Single-layered chrysotile nanotubes: A quantum mechanical ab initio simulation - D’Arco, P.; Noel, Y.; Demichelis, Raffaella; Dovesi, R. (American Institute of Physics, 2009)
Chrysotile single-layered nanotubes, obtained by wrapping the Mg3Si2O5OH4 lizardite monolayeralong the n,-n hexagonal lattice vector, are simulated at the ab initio level by using an all electron6-31G basis set and the B3LYP functional for n varying from 14 to 24 the nanotube radius Rreferred to the oxygen connecting the Mg and Si layers increases from 20 to 35 Å. Because of thefull exploitation of the helical symmetry, recently implemented in the CRYSTAL code, the computational cost for the full self-consistent field SCF and gradient calculation increases only bya factor of 2 and 1.2, respectively, when passing from the lizardite monolayer 18 atoms and 236AOs atomic orbitals in the unit cell to the 24, 24 tube 864 atoms and 11 328 AOs. The total energy of the tubes is always larger than that of the lizardite monolayer; the difference E decreases very rapidly with n; for the largest tube here considered n=24 E is as small as 2.7 kJ/mol per formula unit f.u.; extrapolating to larger n values, at about R=50 Å, E becomes smaller than 1 kJ mol f.u. Very large energy gains are observed for small n values during optimization after rolling, mainly due to the rotation of the SiO4 tetrahedra that are in the inner part of the cylinder “normal rolling”; such a rigid rotation accounts for about 85% of the overall relaxation energy. “Inverserolling” tubes SiO4 on the external wall of the tube are shown to be less stable than the corresponding “normal” tubes.